Stereopsis and depth perception - Parker, AJ (Oxford University Press, 2019)
Humans and some animals can use their two eyes in cooperation to detect and discriminate parts of the visual scene based on depth. Owing to the horizontal separation of the eyes, each eye obtains a slightly different view of the scene in front of the head. These small differences are processed by the nervous system to generate a sense of binocular depth. As humans, we experience an impression of solidity that is fully three-dimensional; this impression is called stereopsis and is what we appreciate when we watch a 3D movie or look into a stereoscopic viewer. While the basic perceptual phenomena of stereoscopic vision have been known for some time, it is mainly within the last 50 years that we have gained an understanding of how the nervous system delivers this sense of depth. This period of research began with the identification of neuronal signals for binocular depth in the primary visual cortex. Building on that finding, subsequent work has traced the signaling pathways for binocular stereoscopic depth forward into extrastriate cortex and further on into cortical areas concerning with sensorimotor integration. Within these pathways, neurons acquire sensitivity to more complex, higher order aspects of stereoscopic depth. Signals relating to the relative depth of visual features can be identified in the extrastriate cortex, which is a form of selectivity not found in the primary visual cortex. Over the same time period, knowledge of the organization of binocular vision in animals that inhabit a wide diversity of ecological niches has substantially increased. The implications of these findings for developmental and adult plasticity of the visual nervous system and onset of the clinical condition of amblyopia are explored in this article. Amblyopic vision is associated with a cluster of different visual and oculomotor symptoms, but the loss of high-quality stereoscopic depth performance is one of the consistent clinical features. Understanding where and how those losses occur in the visual brain is an important goal of current research, for both scientific and clinical reasons.